2000
DOI: 10.1159/000023517
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric Bone Mineral Density in Young Women with Turner’s Syndrome Treated with Estrogens or Estrogens plus Growth Hormone

Abstract: To explore the effects of estrogen replacement therapy (ERT) and recombinant growth hormone (GH) treatment on bone mineral density (BMD) in Turner’s syndrome, we assessed volumetric BMD (vBMD), which is less dependent on body and bone sizes, in these patients at final height. The areal BMD (aBMD) was measured in 26 young women with Turner’s syndrome (age range 17.5–25.0 years) by dual-energy X-ray absorptiometry, and vBMD was calculated. Patients were subdivided as group 1 (n = 12; ERT alone) and group 2 (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 13 publications
3
25
0
Order By: Relevance
“…Therefore, it is not possible to study BMD with the use of DEXA scans without acknowledging the influence of size. A recent study of adolescents calculated volumetric BMD of the spine and found values that were comparable to those of a reference population (145). In an adult population of 60 TS patients, we found slight, but significant reductions in volumetric BMD (vBMD) in the spine, while vBMD at the hip was actually greater in TS compared with an age-matched control group (76).…”
Section: Spontaneous Accretion Of Bone Masssupporting
confidence: 75%
See 2 more Smart Citations
“…Therefore, it is not possible to study BMD with the use of DEXA scans without acknowledging the influence of size. A recent study of adolescents calculated volumetric BMD of the spine and found values that were comparable to those of a reference population (145). In an adult population of 60 TS patients, we found slight, but significant reductions in volumetric BMD (vBMD) in the spine, while vBMD at the hip was actually greater in TS compared with an age-matched control group (76).…”
Section: Spontaneous Accretion Of Bone Masssupporting
confidence: 75%
“…Treatment with estrogens is needed to induce maximal peak bone mass in adolescents and young adults (145,253,258,259). This is supported by four longitudinal studies of estrogen deficient as well as estrogen replete adolescents with TS.…”
Section: Hrt Gh and Bonementioning
confidence: 95%
See 1 more Smart Citation
“…This finding may largely be due to the two-dimensional nature of dual energy x-ray absorptiometry (DEXA) scans (9), which fails to account for the reduced height in TS leading to lower BMD a priori. Studies of volumetric BMD, taking actual body height into account, have shown largely similar volumetric BMD in TS and controls (4,10). Regardless of BMD, end-point studies have documented increased fracture frequency in girls and women with TS (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] Conversely, it was observed that TS patients receiving appropriate oestrogen treatment usually showed normal trabecular BMD after adjusting for body size. [13][14][15][16][17] In addition to Hormonal Replacement Therapy (HRT), Growth Hormone (GH) administration is considered standard treatment for TS girls, but the role of GH in promoting bone accrual has not yet been completely defined. [18][19][20] Several studies reported in TS patients an increase in fracture prevalence and risk that was higher during childhood and after the age of 45.…”
mentioning
confidence: 99%